2013
DOI: 10.1161/strokeaha.112.669853
|View full text |Cite
|
Sign up to set email alerts
|

MR-DWI–Positive Lesions and Symptomatic Ischemic Complications After Coiling of Unruptured Intracranial Aneurysms

Abstract: Downloaded from StrokeMarch 2013 infarction on MR-DWI. The incidence of SIC was 3.5% per patient (14/396). Among the patients who underwent MR-DWI, the incidence of SIC was 4.1% (14/342). All SIC developed within 12 hours posttreatment and were associated with the relevant brain. The ischemic symptoms were most severe at the beginning, but improved with time in all patients. The 1-month modified Rankin Scale scores of the 14 patients were 0 in 6, 1 in 5, 2 in 2, and 3 in 1 patient, respectively. The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 2 publications
6
52
1
Order By: Relevance
“…Diffusion-positive lesions are mostly asymptomatic, but larger or more numerous lesions are associated with ischemic symptoms. 11 This was confirmed in our study with 2 of the 3 patients who had ischemic TIA or stroke with MR imaging scans showing a large number of diffusion lesions. The third patient did not have MR imaging, but an early CT scan and delayed MR imaging showed embolic changes that would certainly have been correlated with a large DWI load.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Diffusion-positive lesions are mostly asymptomatic, but larger or more numerous lesions are associated with ischemic symptoms. 11 This was confirmed in our study with 2 of the 3 patients who had ischemic TIA or stroke with MR imaging scans showing a large number of diffusion lesions. The third patient did not have MR imaging, but an early CT scan and delayed MR imaging showed embolic changes that would certainly have been correlated with a large DWI load.…”
Section: Discussionsupporting
confidence: 82%
“…11,12 They are also increasingly recognized after open and endovascular cardiac interventions. 13,14 The degree to which they are due to gas or thrombotic or other embolic material is unknown; however, the use of heparin and air filters has been shown to reduce their incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Because there were only a small number (n ϭ 2) of symptomatic lesions in this study population, we assumed that multiple lesions (n Ն 6) were more severe lesions. 5 Additionally, the degree of embolization was determined by immediate postprocedural MR imaging.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] To reduce thromboembolic complications, many studies investigated the association between thromboembolism and aneurysm and/or patient factors. [5][6][7][8] Previous studies have demonstrated that 30%-60% of endovascular coil embolizations for unruptured aneurysms show ischemic lesions on postprocedural diffusion-weighted images. Although most of the lesions seem to be benign, some could result in permanent neurologic sequelae.…”
mentioning
confidence: 99%
“…[2][3][4]8,9,15,22,[24][25][26] Most patients who show HSI spots are asymptomatic, and the clinical significance of such spots remains controversial. However, the HSI spots reflect the presence of damaged tissue, 5,7,12,15 and their associated potential risks cannot be ignored.This study was conducted to analyze the current incidence of postprocedural DWI HSI lesions at our institution and to explore the possible risk factors for microembolic lesions visible as HSI spots on DWI after endovascular coiling of UIAs. …”
mentioning
confidence: 99%